Genetic Identification of a PilT Motor in Geobacter sulfurreducens Reveals a Role for Pilus Retraction in Extracellular Electron Transfer - Speers, Allison M.; Schindler, Bryan D.; Hwang, Jihwan; Genc, Aycin; Reguera, Gemma (Frontiers in Microbiology, 2016)
The metal-reducing bacterium Geobacter sulfurreducens requires the expression of conductive pili to reduce iron oxides and to wire electroactive biofilms, but the role of pilus retraction in these functions has remained elusive. Here we show that of the four PilT proteins encoded in the genome of G. sulfurreducens, PilT3 powered pilus retraction in planktonic cells of a PilT-deficient strain of P. aeruginosa and restored the dense mutant biofilms to wild-type levels. Furthermore, PilT3 and PilT4 rescued the twitching motility defect of the PilT-deficient mutant. However, PilT4 was the only paralogue whose inactivation in G. sulfurreducens lead to phenotypes associated with the hyperpiliation of non-retractile mutants such as enhanced adhesion and biofilm-forming abilities. In addition, PilT4 was required to reduce iron oxides. Taken together, the results indicate that PilT4 is the motor ATPase of G. sulfurreducens pili and reveal a previously unrecognized role for pilus retraction in extracellular electron transfer, a strategy that confers on Geobacter spp. an adaptive advantage for metal reduction in the natural environment.